Green Organization - Arrived in companies or still a vision? An exploratory study based on an expert survey on the significance of sustainability and the implementation of sustainability management in companies - Ludin, Daniela; Arngold, Christina; Mueller, Erika; Wellbrock, Wanja (Oeconomica Jadertina, 2024)
Scientists and activists have been taking part in the sustainability debate for decades and calling for a rethink in politics and society. A change is becoming noticeable that is also having an impact on companies. They cannot avoid dealing with the issue of sustainability, as internal and external stakeholders exert pressure on them due to their interests. Based on an online survey, this explorative empirical study identifies and analyses what companies understand by the term "sustainability" and what importance is currently attached to sustainability management in companies. In addition, the main advantages of sustainable management for companies and obstacles to the implementation of sustainability in companies are also identified. The results of the study show that sustainability is of great importance to the companies surveyed. For the most part, companies have an understanding of sustainability. Reasons for "sustainable entrepreneurship" are based in particular on economic and "green" motives; the main reason is therefore to improve the image of the companies. The main obstacles to implementing "sustainable entrepreneurship" are the time required, the high costs and uncertainty about the economic benefits. The sustainability requirements are hardly or only partially perceived as a burden. Corporate goals and guidelines together form an important factor in establishing sustainability in the organizational culture. Companies voluntarily align themselves partially or completely with standardized environmental management norms.
Keywords: green organization, sustainability, sustainability management